Palaeomagnetism of middle proterozoic basic intrusives in central sweden and the fennoscandian apparent polar wander path (Dataset) ... - Bylund, Göran (Magnetics Information Consortium (MagIC), 2006)
Paleomagnetic, rock magnetic, or geomagnetic data found in the MagIC data repository from a paper titled: Palaeomagnetism of middle proterozoic basic intrusives in central sweden and the fennoscandian apparent polar wander path ...